Burden of heart failure in Asian Countries from 1990 to 2021: Update from the Global Burden of Disease Study 2021 - Chaofeng Niu; Donghua Xue; Juwei Dong; Qiwen Yang; Peiyu Zhang; Lan Wei; Nina Wang; Meng Li; Lijing Zhang (PLoS ONE, 2026)
Heart failure (HF) remains a major public health challenge in Asia, with rising prevalence and disability burden. This study analyzed data from the 2021 Global Burden of Disease study (GBD 2021) to assess HF trends across 48 Asian countries from 1990 to 2021. In 2021, there were 29.5 million HF cases in Asia, a 155% increase since 1990, with an age-standardized prevalence rate rising from 583.62 to 633.76 per 100,000. Years lived with disability (YLDs) also surged by 155%, reaching 2.86 million in 2021. China accounted for 44.34% of Asia’s HF cases, with the highest YLDs. Treated HF cases were most common, but severe HF contributed most to YLDs. The middle-high socio-demographic index (SDI) region had the highest age-standardized prevalence rate, while most SDI regions saw increasing trends, except Japan and Cyprus. The findings highlight the growing HF burden in Asia, urging targeted interventions to address this escalating health crisis.